Teacher Development: Strategies and Perception - Bharati, Padam Lal; Chalise, Subas (Saptagandaki Journal, 2017)
Aspects of teachers’ professional development in general and EFL teachers in non-English speaking countries in particular are issues that warrant constant research. Although these are widely researched areas internationally, within Nepal grounded professional development studies have been sparsely carried out. A considerable section of practicing English language teachers has no clear idea of the issue although it directly concerns themselves. Against this backdrop, this article explores some EFL teachers’ perception on the concept of teacher development in a relatively sophisticated centrally located town of Nepal. The Saptagandaki Journal Vol.8 2017: 69-78